2004
DOI: 10.1046/j.0305-182x.2003.01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Single tooth bite forces in healthy young adults

Abstract: summary  The assessment of bite forces on healthy single tooth appears essential for a correct quantification of the actual impact of single implant oral rehabilitations. In the present study, a new single tooth strain‐gauge bite transducer was used in 52 healthy young adults (36 men, 16 women) with a complete permanent dentition. The influences of tooth position along the dental arch, of side, and of sex, on maximum bite force were assessed by an anova. No significant left–right differences were found. On ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
203
11
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(243 citation statements)
references
References 22 publications
(62 reference statements)
18
203
11
11
Order By: Relevance
“…Autores como Ferrario et al (2004), encontraron que las fuerzas oclusales de un solo diente en hombres adultos sanos fueron de 150 y 140 N para los incisivos centrales y laterales respectivamente. Gibbs et al (1981) declararon que las cargas oclusales son de 263 N durante la masticación normal.…”
Section: Discussionunclassified
“…Autores como Ferrario et al (2004), encontraron que las fuerzas oclusales de un solo diente en hombres adultos sanos fueron de 150 y 140 N para los incisivos centrales y laterales respectivamente. Gibbs et al (1981) declararon que las cargas oclusales son de 263 N durante la masticación normal.…”
Section: Discussionunclassified
“…The maximum bite force and single tooth bite force in the premolar region have been reported to be 246-398 N 13) and 179-291 N 14) respectively. The failure loads obtained for all the groups in this study were greater than these values.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrario et al 35) studied single-tooth bite forces in healthy young adults, and they reported results of 250 and 290 N for the first and second premolars, respectively, in men. Greater bite forces must be expected in subjects with functional disturbances, such as bruxism 36) .…”
Section: Discussionmentioning
confidence: 99%